TMS pulse propagates beginning in the axon terminal, subsequently activating soma and dendrites. - Nicholas Hananeia (22683665) (2025)
Propagation of an action potential induced by a 250 V/m monophasic TMS pulse. (a): Voltage trace at various recording locations showing initiation of action potential at axon terminal (b): Schematic of cell showing the recording locations. (TIFF)